Compulsory first year core courses that embed core online and university literacies. - Lawrence, Jill; Ploetz, Leanne (Australia. Dept of Education and Training (DET), 2018)
The University of Southern Queensland (USQ) case study for project SP14-4602 investigated whether two core first year nursing courses positively enhanced nursing students' confidence and competence as they made their transition to the new university culture. The data revealed that the two embedded and scaffolded courses assisted first year nursing students to become more familiar with the often unfamiliar and largely online regional university environment and to feel more confident as they attempted to engage and master the literacies they encountered there. A summary report is also available, titled: Embedded and scaffolded course design enhances students’ online learning experiences.